2009
DOI: 10.1111/j.1440-1797.2009.01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Progress of treatment in ANCA‐associated vasculitis

Abstract: This study reports on innovations in the field of, and current approaches to, the therapy of ANCA-associated vasculitis (AAV). Randomized clinical trials and prospective open label trial of newer therapies performed in the last 15 years in Wegener's granulomatosis and microscopic polyangiitis or both (AAV) were reviewed. Although cyclophosphamide remains the favoured immunosuppressive for remission induction, the use of alternative immunosuppressives and of intravenous pulsed administration have reduced cyclop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 67 publications
(131 reference statements)
1
29
0
3
Order By: Relevance
“…Several patients developed vague symptoms such as fatigue, aches, and malaise with steroid cessation, raising a differential diagnosis of mild secondary adrenal insufficiency versus low-grade AAV-in each case, symptoms resolved with reinitiation of low-dose prednisone. To date, insufficient data remain regarding dosing and duration of steroid therapy in AAV (28). None of the clinical flares were preceded by a rising ANCA titer or repopulation of circulating B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several patients developed vague symptoms such as fatigue, aches, and malaise with steroid cessation, raising a differential diagnosis of mild secondary adrenal insufficiency versus low-grade AAV-in each case, symptoms resolved with reinitiation of low-dose prednisone. To date, insufficient data remain regarding dosing and duration of steroid therapy in AAV (28). None of the clinical flares were preceded by a rising ANCA titer or repopulation of circulating B cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, randomized clinical trials of new therapies for AAV have been performed in Europe and the USA. On the principle that more severe disease requires more aggressive therapy, EUVAS devised a system for subgrouping AAV presentations, for example, based on the severity of renal impairment, for different regimens [44] . Results of such trials are very informative and might lead to consensus recommendations on how to AAV/PRV should be treated depending on the types, the disease severity and age.…”
Section: Outcome and Treatmentmentioning
confidence: 99%
“…p-ANCA is a serum autoantibody, which could be detected in vasculitis [22], systemic lupus erythematosus [23], and SJS [24]. Several lines of evidences had demonstrated that p-ANCA is associated with vasculitic polyneuropathy, as we did in this cohort study [25–27].…”
Section: Discussionmentioning
confidence: 60%